A new genus and two new species of soldier fly (Diptera: Stratiomyidae: Chiromyzinae) from Australia, one found infesting sugarcane in central Queensland - Daniels, Greg (Zootaxa, 2016)
Metridius nov. gen. and types species M. robertsoni nov. sp. with winged males and apterous females is described from adults and larvae found infesting sugarcane stools from near Mackay, central Queensland. A second new species, M. mcalpinei nov. sp., based only on males from near Sydney, New South Wales is also described. Notes on the biology of both species and an identification key to the genera of the subfamily Chiromyzinae and to the species are also given.